Peran Pemerintah Terhadap Pengembangan Sektor Pariwisata di Kabupaten Biak Numfor - Endah Dwi Lestari; Yoseb Boari; Melyanus Bonsapia; Silas Marcelino Anes (Journal of Economics Review (JOER), 2023)
The purpose of this study is to determine the government's role in the development of the tourism sector in Biak Numfor Regency. The method used in this research is a qualitative approach. The results of the study show that there are four tourism sector development programs in Biak Numfor Regency. The four programs include; tourism destination development programs, tourism marketing development programs, partnership development programs and tourism facilities and infrastructure development programs. These development programs are the main development programs carried out by the tourism office for the development of tourist objects in Biak Numfor Regency.